COMPARATIVE STUDY ON ERGONOMICALLY DESIGNED SCHOOL BAGS AND TRADITIONAL SCHOOL BAGS - Dr. B. Sathya Jebasinghrajan (International Journal For Research In Educational Studies, 2025)
The impact of school bag design on students' musculoskeletal health is a growing concern. This study evaluates the ergonomic benefits of the REHOB Ergonomically Designed School Bag in comparison to traditional school bags. A research trial was conducted among 20 school children to assess comfort, posture, and usability. The results indicate that the REHOB bag provides superior comfort, promotes better posture, and reduces strain on the back and shoulders, thereby improving the overall well-being of students.